2012
DOI: 10.1097/brs.0b013e3182269b19
|View full text |Cite
|
Sign up to set email alerts
|

The Angiogenic Capacity From Ligamentum Flavum Subsequent to Inflammation

Abstract: LF cells interact with macrophage-like cells to produce angiogenesis-related factors except TGF-β1. Activated LF cells that have been exposed to macrophage, can impact the inducement of angiogenesis-related factors, suggesting that fibrosis and scarring during inflammatory reaction is the major pathomechanism of LF hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Attention has recently focused on angiogenesis, a pivotal component of scarring and the tissue repair process. Moon et al [40] reported that LF cells interact with macrophage-like cells to produce angiogenesis-related factors, with the exception of transforming growth factor β1. Activated LF cells exposed to macrophages can impact the stimulus of angiogenesis-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Attention has recently focused on angiogenesis, a pivotal component of scarring and the tissue repair process. Moon et al [40] reported that LF cells interact with macrophage-like cells to produce angiogenesis-related factors, with the exception of transforming growth factor β1. Activated LF cells exposed to macrophages can impact the stimulus of angiogenesis-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies supported that LF hypertrophy is a major pathogenic factor of central LSS4,12,22), and that LF hypertrophy has close relationship with mechanical stress2,7,9,10,16). Furthermore, repetitive (longer duration) wide motion (wide segmental angulation) in maximal stenotic level could be considered as high mechanical stress that may lead to development of LF hypertrophy7). Together, the results suggest that even though there are several factors that may be related to the development of central LSS, LF hypertrophy could be the major anatomical causes of RNRs formation in central LSS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The major causes of LSCS are aberrant osteophyte formation within the facet joints, disc protrusion, and hypertrophy of the ligamentum flavum (LF) [1][3]. The LF covers most of the posterior and lateral part of the spinal canal; therefore, LF hypertrophy contributes directly to mechanical compression of the nerve root or cauda equina, or indirectly to vascular insufficiency, which leads to inadequate blood flow and oxygenation [2], [4], [5]. Several studies have investigated the mechanism underlying LF hypertrophy, but the mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Several growth factors and inflammatory cytokines, such as transforming growth factor (TGF)-β1, participate in the pathological processes [2], [4], [5], [7][10]. TGF-β1 is a key factor in tissue fibrosis [11][15] and is abundantly expressed in hypertrophied degenerative LF tissues from LSCS patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation